EFEKTIFITAS PEMBELAJARAN BERBASIS GAMIFIKASI TERHADAP KETERAMPILAN MEMBACA SISWA KELAS II SD AL-AMANAH MOJOGEDANG TAHUN PELAJARAN 2025/2026 - Muti'ah, Erlis; Elinda Rizkasari; Ani Restuningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This quantitative study evaluated the comparative efficacy of gamified learning versus traditional instruction in enhancing primary school students' reading comprehension skills. Utilizing a quasi-experimental non-equivalent control group design, the research examined 50 second-grade students ( experimental group;  control group). Data were collected using reading comprehension assessments administered prior to (pre-test) and following (post-test) the intervention. Analytical procedures encompassed descriptive statistics, parametric assumption checks, an independent sample t-test, and Normalized Gain (N-Gain) metrics. Descriptive results revealed post-intervention mean scores of  for the experimental cohort and  for the control cohort, with both groups exhibiting moderate learning gains (N-Gain =  and , respectively). Inferential testing demonstrated no statistically significant difference in reading comprehension outcomes between the two instructional approaches (, Cohen's ). These findings indicate that gamification and traditional direct instruction yield comparable cognitive efficacy in early-grade reading literacy. Consequently, educators should carefully balance gamification elements with cognitive load considerations rather than assuming an inherent superiority of gamified instruction over traditional methods.